2017
DOI: 10.1016/j.ins.2017.08.070
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic method of intuitionistic fuzzy MCDM to assist the hierarchical medical system in China

Abstract: Thermodynamics is of knowledge structure to depict the stability (or instability) of a system effectively. For the increasing complexity of the application problems and the fuzzy nature of human thought, intuitionistic fuzzy sets were proposed and have become a powerful tool to portray the uncertainty of things. In order to best utilize decision information to solve the multi-criteria decision making (MCDM) problems in an intuitionistic fuzzy environment, the paper proposes a thermodynamic method for MCDM with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…They furtherly combined the weighted averaging operator and the TOPSIS method to simulate the medical system in West China Hospital. They showed that the thermodynamics model clearly portrays the fuzziness of the hierarchical medical system in China and reflected the quantity and the quality of decision process [35]. Zheng et al established a new evaluation indicator system for hierarchical medical policies based on observation time.…”
Section: Introductionmentioning
confidence: 99%
“…They furtherly combined the weighted averaging operator and the TOPSIS method to simulate the medical system in West China Hospital. They showed that the thermodynamics model clearly portrays the fuzziness of the hierarchical medical system in China and reflected the quantity and the quality of decision process [35]. Zheng et al established a new evaluation indicator system for hierarchical medical policies based on observation time.…”
Section: Introductionmentioning
confidence: 99%
“…It was not until the end of 2018 that the trial of "hierarchical medical system" was launched [52]. Another example, public hospitals have been the focus of the new health reform since 2012, and the " canceling medicine markups" is the main key point, but until 2017, it was fully implemented in public hospitals [53].…”
Section: Resultsmentioning
confidence: 99%
“…Verma and Rajasankar [2] innovatively proposed a thermodynamically consistent model for MCDM using the analogies for thermodynamic indicators. Ren et al [10,11] extended the thermodynamic method to some fuzzy context and applied it for emergency decision making. Thermodynamic method is based on three laws of thermodynamics: the concepts of energy, exergy, and entropy [2].…”
Section: Thermodynamicsmentioning
confidence: 99%
“…Verma and Rajasankar [2] first introduced the thermodynamic method to solve MCDM problems. Inspired by Verma and Rajasankar's [2] innovative work, Ren et al [10,11] extended the thermodynamic method to intuitionistic fuzzy context and hesitant fuzzy context.…”
Section: Introductionmentioning
confidence: 99%